The OsAP4-OsCATA/OsCATC Regulatory Module Orchestrates Drought Stress Adaptation in Rice Seedlings Through ROS Scavenging - Yifei Jiang; Bin Xie; Xiong Luo; Yangsheng Li (Plants, 2025)
Drought stress poses a major constraint on global crop productivity. Although aspartic proteases (APs) are primarily characterized in plant disease resistance, their roles in abiotic stress adaptation remain largely unexplored. Here, we demonstrate that rice (Oryza sativa) OsAP4 critically regulates drought stress tolerance at the seedling stage. Genetic manipulation through overexpression (OsAP4-OE) or CRISPR knockout (OsAP4-KO) resulted in significantly reduced or enhanced stress tolerance compared to wild-type plants, respectively. Through integrated approaches including yeast two-hybrid, bimolecular fluorescence complementation, pull-down, co-immunoprecipitation, and protein degradation assays, we established that OsAP4 physically interacts with and destabilizes OsCATA/OsCATC, two catalase enzymes responsible for reactive oxygen species (ROS) scavenging. Importantly, OsAP4 modulates ROS production under drought stress treatment conditions. Together, these findings reveal a novel OsAP4-OsCATA/OsCATC regulatory module governing rice drought stress responses.